Exploring the Relationship Between Children's Engineering Habits of Mind and Teachers' Engineering Teaching Self-Efficacy - Erol, Ahmet; Erol, Mustafa (SPRINGER, 2026)
This study had three main objectives. First, it aimed to develop the Primary School Engineering Habits of Mind (P-EHoM) scale for primary school children. Second, it aimed to adapt the Teaching Engineering Self-Efficacy Scale (TESS) into Turkish for use with primary school teachers. Third, it aimed to explore the relationship between children's engineering habits of mind (EHoM) and teachers' engineering teaching self-efficacy (TES). The study's participants consisted of 941 primary school children and 607 primary school teachers. Data were collected through the P-EHoM and TESS. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and Pearson correlation analysis were employed to analyze the data. The findings revealed that the P-EHoM scale is valid and reliable for assessing children's EHoM. Moreover, the TESS was valid and reliable for evaluating teachers' TES within Turkish culture. Additionally, a moderate positive relationship was found between children's EHoM and teachers' TES. These findings contribute to the growing literature on engineering education in primary school settings.
Keywords: Engineering habits of mind; Engineering self-efficacy; Primary school students; Teachers; FIT INDEXES; K-12 TEACHERS; STEM; THINKING; DESIGN; SCALE; Education & Educational Research